Optimal Management of Formation of Digital Competencies of Personnel of Organizations for the Purposes of Ensuring National Technological Sovereignty - Alexander A. Chursin; Andrey A. Efremov; Sergey V. Nazyuta (RUDN Journal of Economics)
As part of the implementation of the concept of achieving national technological sovereignty at the micro level, staffing is required for the digital transformation of key business processes of organizations. The most important element of this process is the formation of digital competencies of personnel, primarily in advanced production. In this vein, one of the most popular tools is the methodology for optimal management of the development of digital competencies, its economic justification and mathematical implementation. This article is devoted to solving this scientific and practical problem. The emphasis is on the essence of digital competencies and their classification. The author’s mathematical model for managing the development of digital competencies of the organization’s personnel has been developed, and its substantive analysis is given. The main directions for the practical application of this model and the development on its basis of recommendations for making effective management decisions are outlined.